Development of the Impact of Juvenile Metachromatic Leukodystrophy on Physical Activities scale - T. Michelle Brown; Susan Martin; Sheri E. Fehnel; Linda S. Deal (SpringerOpen, 2018)
Abstract Background Metachromatic leukodystrophy (MLD) is a rare disease with three forms based on the age at onset of signs and symptoms. The objective of this study was to develop a caregiver-reported clinical outcome assessment that measures impairments in physical functioning related to activities of daily living in patients with juvenile MLD. Methods A targeted literature review and exploration of proprietary research, including a conceptual model, were conducted. Concept elicitation interviews were conducted to elicit additional concepts related to impairments in patients' physical functioning with caregivers of five individuals with juvenile MLD. Based on the research review and concept elicitation interviews, the conceptual model was updated and the Impact of Juvenile Metachromatic Leukodystrophy on Physical Activities (IMPA) scale draft items were created. Cognitive debriefing interviews were conducted with six additional caregivers to finalize the conceptual model and to refine the IMPA scale. Results Initially, 17 potentially important concepts were identified and addressed in the draft IMPA scale. Following the cognitive debriefing interviews, 15 activities/items remained: brush teeth, comb/brush hair, bathe/shower, dress self, eat, drink, use pencil/crayon, sit upright, use toilet, get on/off toilet, walk, use stairs, get in/out of bed, get in/out of chair/wheelchair, and get in/out of vehicle. Items that did not uniquely contribute to the purpose of the instrument were removed. Conclusion The IMPA scale, developed according to regulatory standards, provides a means of detecting changes in activities of daily living in individuals with juvenile MLD and can hence be used in future studies to measure benefits of therapeutic interventions.